2009
DOI: 10.1111/j.1600-051x.2009.01386.x
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based study on the association between type 2 diabetes and periodontal disease in 12,123 middle‐aged Taiwanese (KCIS No. 21)

Abstract: The association between T2DM and the risk for PD among young adult was demonstrated. This finding, together with other aetiological factors, fit with the current hypothesized model of the aetiology of periodontitis. However, the effect of T2DM modified by waist measurement should be verified in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 33 publications
3
35
0
2
Order By: Relevance
“…Overall, the risk for periodontal care was ≈18% higher among those with than among those without diabetes. These findings are consistent with those of other studies in which various aspects of periodontal health and diabetes or metabolic syndrome have been examined 1,7‐9,25‐29 . For example, in the NHANES III study (The Third National Health and Nutrition Examination Study), the prevalence of periodontitis among those with versus without diabetes was 31.3% versus 10.6% among African Americans, 28.5% versus 5.9% among Mexican Americans, and 22.3% versus 6.2% among whites 3 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, the risk for periodontal care was ≈18% higher among those with than among those without diabetes. These findings are consistent with those of other studies in which various aspects of periodontal health and diabetes or metabolic syndrome have been examined 1,7‐9,25‐29 . For example, in the NHANES III study (The Third National Health and Nutrition Examination Study), the prevalence of periodontitis among those with versus without diabetes was 31.3% versus 10.6% among African Americans, 28.5% versus 5.9% among Mexican Americans, and 22.3% versus 6.2% among whites 3 .…”
Section: Discussionsupporting
confidence: 89%
“…Periodontitis is associated with a variety of adverse dental outcomes, including destruction of the underlying bone, tooth loosening, and, if left untreated, edentulism 5 . Numerous studies have evaluated the association between diabetes and periodontitis, a chronic infectious and inflammatory process 6‐12 . Diabetes is a generally accepted risk factor for periodontal disease, 6 and periodontitis is sometimes considered the “sixth complication” of diabetes 13 .…”
mentioning
confidence: 99%
“…Since both diabetes groups (T1D and T2D) were on average younger than the older study population of the DMS IV, it can be concluded that diabetes may enhance periodontal destruction and may act as a predisposing factor for periodontitis. The negative influence of diabetes on periodontal health, which was the subject of clinical trials [39,40], review articles [27,28], and meta-analyses [29,41], is now generally accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Many evidences support the idea that the link between periodontal disease and diabetes is biunivocal [77,78]. Although over-expression of inflammatory mediators in crevicular fluid is frequently reported, no significant difference in periodontal pathogens is observed [79,80].…”
Section: Diabetes and Periodontitismentioning
confidence: 95%